Analysis of the feasibility of fishing using push net fishing gear - Lana Izzul Azkia; Muhammad Reza (JURNAL MINA SAINS, 2023)
Fishing activities using sondong fishing gear are classified as small-scale, with the main catch being shrimp. Shrimp is a fishery commodity that has high economic value, so fishing activities using this fishing gear should provide profits. However, it is currently unknown whether this fishing activity benefits fishermen. The research aims to assess the feasibility of using sodong fishing gear in Babalan Village, Demak, Central Java. The method used is a survey with direct interview techniques to fishermen using a questionnaire. The research sample used was 30 fishermen who were chosen randomly. Data analysis uses cost, income, profit, Revenue Cost Ratio, Benefit Cost Ratio, Payback Period, Net Present Value, and Internal Rate of Return analysis. The research results show that the average investment cost incurred by fishermen is IDR. 17,000,000. The total costs incurred in 1 year average Rp. 105,244,000. The income and profits earned differ in each season. The R/C value for each season from this fishing effort is >1, meaning this business is feasible and provides profits. The Net B/C value of this business is 5.9, meaning this business is feasible. Payback period analysis shows a return on capital of 9 months. The NPV value in this fishing effort is positive. The IRR value is 8.15% > 7% interest rate.